Integrasi Kurikulum Tahfidz Al-Qur'an Dengan Pendidikan Formal di PPTQ Nurul Istiqlal Wonosari Klaten: Penelitian - Lukianto, Fahmi Azis; Rosjid, Fauzal Maula L; gifari, Buyung Al; Suryo, Khuriyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The integration of the Al-Qur'an memorization curriculum with formal education is one of the Islamic education models that integrates Al-Qur'an memorization learning with the national curriculum. This study aims to analyze the implementation of the integration of the Al-Qur'an memorization curriculum with formal education at the Nurul Istiqlal Al-Qur'an Memorization Islamic Boarding School (PPTQ) in Wonosari, Klaten. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that PPTQ Nurul Istiqlal applies a curriculum integration system that combines Al-Qur'an memorization learning with the formal education curriculum in a balanced manner. This integration model includes aspects of time management, learning methods, evaluation, and adequate support for facilities and infrastructure. The implementation of this curriculum integration provides a positive contribution to the achievement of students' competencies in both cognitive, affective, and psychomotor aspects.